Emulation of ARISTOTLE and ROCKET AF trials in real-world atrial fibrillation patients results in similar efficacy and safety as original landmark trials: insights from the GARFIELD-AF registry - Ralf E Harskamp; Karen Pieper; A John Camm; Ajay K Kakkar; Jelle C L Himmelreich; Saverio Virdone; Jean-Pierre Bassand; Frank Misselwitz; Freek W A Verheugt; Frank Cools; Harry Gibbs; Antônio C Pereira-Barretto (Open Heart)
Aims This study aimed to determine the robustness, reproducibility and representativeness of the landmark Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (AF) (ARISTOTLE) and Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in AF (ROCKET AF) randomised trials through replication in an observational AF patient registry.Methods and results Patients from the Global Anticoagulant Registry in the FIELD (GARFIELD)-AF registry treated with apixaban, rivaroxaban or vitamin K antagonist (VKA) were assessed for eligibility for the ARISTOTLE and ROCKET AF trials. HRs of apixaban and rivaroxaban versus comparator for stroke/systemic embolism, major bleeding and all-cause mortality within 2 years follow-up were calculated using propensity score overlap-weighted Cox models. Among GARFIELD-AF patients on apixaban, 2570/3615 (71%) would have been eligible for ARISTOTLE. Among patients using rivaroxaban, 2005/4914 (41%) would have been eligible for ROCKET AF. Eligibility rates were steady over time, with minor differences across medical specialties. Real-world AF patients selected according to trial criteria had lower cardiovascular burden than the original trial participants, especially compared with ROCKET AF. HRs (95% CI) for apixaban versus VKA among ARISTOTLE-eligible users were 0.57 (0.34 to 0.94) for stroke/systemic embolism, 0.76 (0.48 to 1.20) for major bleeding and 0.89 (0.70 to 1.12) for all-cause mortality. Among ROCKET AF-eligible rivaroxaban users, HRs for rivaroxaban versus VKA were 0.90 (0.57 to 1.43), 0.92 (0.59 to 1.43) and 0.86 (0.69 to 1.08), respectively. All safety and efficacy estimates were similar to those in the original trials.Conclusion Real-world representativeness of the selection criteria was greater for ARISTOTLE than ROCKET AF. The pivotal randomised trials of apixaban and rivaroxaban versus warfarin can be successfully emulated in real-world AF patients by applying trial-specific selection criteria and appropriate methodology for non-randomised treatment allocation.Trial registration number NCT01090362.